Tourism-Based Learning Model: Introduce Local Culture to the Global Community - Fajrin, Nilamsari Damayanti; Setyawan, Agung; Maula, Qurrotu Inayatil (Widyagogik, 2024)
Contextual and meaningful learning is limitedly implemented in elementary schools. Whereas the learning activities stated by the Merdeka Curriculum are not only limited to learning conventionally in class but also involve various activities, such as doing a project. Furthermore, learning activities in the Merdeka Curriculum include a project called Proyek Penguatan Profil Pelajar Pancasila, or Reinforcement Project of Pancasila Student Profile (P5). Regarding the problem, this study is aimed at developing a tourism-based learning model that involves local tourism content in its implementation. To implement the dimension of P5 called global unity in diversity, this learning model was integrated into English. The model was developed by using research and development design with define, design, develop, and disseminate (4D). As a result, the syntax of this learning model includes: 1) orientation, 2) inquiry process, 3) field study or outing class, 4) data analysis, 5) exhibition, and 6) reflection. This learning model was proven to be very good by material experts and practitioners. The students also revealed that this learning model was interesting and fun. They could also work collaboratively, actively, and creatively. Finally, it is expected that the students can use their English skills to promote local tourism.